Examining Various Interpretations of Grice's Cooperative Principle - Dwi Tirta Syafitri, Yona; Budiarti, Vira; Simamora, Afriyanti; Aprilya, Rizka (Elsya : Journal of English Language Studies, 2019)
This study aims to examine various interpretations of the principle of cooperation. The principle of cooperation (CP) was first proposed by H.P. Grice in a series of lectures given in 1967. Grice's most influential contribution to linguistics was his theory of implicature. He illustrated that communication follows what he calls the Cooperative Principle (CP) and argues that the fundamental assumption we make when we speak is that we try to work together to build meaningful conversations (1975). The principle of Grice's Cooperation has become controversial in pragmatics. The main source of controversy related to CP is that the term "cooperation" is open to different interpretations. This article uses descriptive qualitative methods. As for the results of the study of this article, the principle of cooperation has always tended to focus too much on the term 'cooperation', rather than looking at and examining the principle titles for motivation given by Grice to the mechanisms that he has identified.